A study into the hub performance Emirates, Etihad Airways and Qatar Airways and their competitive position against the major European hubbing airlines - O'Connell, John F.; Bueno, Oriol Escofet (Elsevier, 2016)
Arabian Gulf carriers are changing the dynamics of international aviation. While travellers flying between East and West used to connect traditionally at European hubs, the rapid emergence and growth of Emirates, Etihad Airways and Qatar Airways have altered traffic flows, transforming their home bases into global air transport hubs. Thus, this study aims to assess the hub-and-spoke system efficiency of the three main Gulf carriers and compare it to major European hubbing airlines. The paper detects that the connectivity through European hubs is being increasingly challenged by the Gulf based hubs. The research findings have shown a high degree of connectivity and temporal coordination for Gulf carriers, clearly greater than European hubs. Qatar Airways and Etihad Airways provide about twice the level of intercontinental connectivity compared to their European counterparts.
Keywords: Middle east; Gulf carriers; Hub and spoke; Connectivity